2013
DOI: 10.3389/fnhum.2013.00632
|View full text |Cite
|
Sign up to set email alerts
|

How you perceive threat determines your behavior

Abstract: The prioritization of processing emotional stimuli usually produces deleterious effects on task performance when it distracts from a task. One common explanation is that brain resources are consumed by emotional stimuli, diverting resources away from executing the task. Viewing unpleasant stimuli also generates defensive reactions, and these responses may be at least partially responsible for the effect of the emotional modulation observed in various reaction time (RT) paradigms. We investigated whether modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 69 publications
3
40
2
Order By: Relevance
“…First, we did not observe clear support for a valence by context interaction pattern in the RT data. Whereas we observed a reduction in RT when performing a task in the directed towards context in our previous behavioral study (Fernandes et al, 2013), evidence for this modulation effect was modest here. This difference is possibly due to the smaller sample size used in the current fMRI study, which also compromises the statistical power to detect such interaction effects in a voxelwise analysis.…”
Section: Limitationscontrasting
confidence: 91%
“…First, we did not observe clear support for a valence by context interaction pattern in the RT data. Whereas we observed a reduction in RT when performing a task in the directed towards context in our previous behavioral study (Fernandes et al, 2013), evidence for this modulation effect was modest here. This difference is possibly due to the smaller sample size used in the current fMRI study, which also compromises the statistical power to detect such interaction effects in a voxelwise analysis.…”
Section: Limitationscontrasting
confidence: 91%
“…Following this rationale, the directed-toward stimuli probably evoked a more consistent pattern of brain responses across participants, resulting in the failure of the regression model to predict the NA trait. A previous study by Fernandes et al (2013) showed that the threat directed toward the observer is considered as more intense, near, inescapable and with less possibility of hiding by the participants. Thus, it is likely that the increase in the magnitude of threat perception produced patterns of brain activities that were more homogeneous and less susceptible to individual variability.…”
Section: Discussionmentioning
confidence: 96%
“…However, also threatening man-made objects, such as firearms, have been found to trigger behavioral freezing (Fernandes et al, 2013). In research on human freezing, freezing has been found to be evident from bradycardia (i.e., decreased heart rate; Roelofs, Hagenaars, & Stins, 2010), decreased response times (Sagliano, Cappuccio, Trojano, & Conson, 2014;Fernandes et al, 2013), and also from decreased body sway (Roelofs, Hagenaars, & Stins, 2010).…”
Section: Behavioral Immobility Reflects Freezingmentioning
confidence: 99%
“…Based on the finding that reduced response speed is a reliable indicator of freezing (cfr., Sagliano, Cappuccio, Trojano, & Conson, 2014;Fernandes et al, 2013) we operationalized freezing in terms of the speed with which participants clicked a series of radio buttons using their computer mouse. We expected that clicking radio buttons would be slowest in the face of the high building situated close-by.…”
Section: Pilot Study 1bmentioning
confidence: 99%